Analisa Jejaring Sosial dan Retorika Deliberatif - Chandra, Galih (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
The aim of this research is to examine the phenomenon of deliberative rhetoric using the hashtag #SepakatDamai on Twitter to motivate the public. After the tragedy of riots between football supporters at the Kanjuruhan Stadium, it succeeded in triggering public attention and became a trending topic on Twitter. Many football supporters and the general public take an active role in voicing peace to reduce fighting. Through the hashtag #SepakatDamai, the public is persuaded to get involved in carrying out peace agreement actions so that, in the future, there will no longer be any hostility between football supporters. In the end, tweets from actors involved in peaceful demonstrations form social network patterns that can be utilized in deliberative rhetorical actions. The hashtag #SepakatDamai plays a role in mobilizing public opinion support for the peace agreement between football supporters. This discussion emerged spontaneously on Twitter and was widely discussed until it became a trending Twitter topic. This research uses the Social Network Analysis (SNA) method and then connects it with the Digital Movement of Opinion and Rhetoric Theory. This research stage began by determining the most dominant actor in the hashtag #SepakatDamai. After that, the researcher carried out an analysis of the posts made by that actor to determine the rhetorical phenomenon. The results of this research found that the hashtag #SepakatDamai succeeded in mobilizing public opinion about the football supporters' peace agreement. The most dominant actor is @mafiawasit, with a network structure value of degree 1.471, closeness 1.0, betweenness 0.000238, and eigenvector 1.0. The @mafiawasit account carries out deliberative rhetoric for the public by showing the facts that have occurred regarding the peace agreement between football supporters through posts on Twitter and retweeting similar posts so that the public follows the peaceful demonstration.